IMPROVING STUDENTS’ SKILL IN WRITING RECOUNT TEXT BY USING PEER REVIEW TECHNIQUE (A Classroom Action Research of the Eighth Grade Students of SMP N 4 Batang Year 2014/2015) (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2015)
This study was conducted based on the fact that writing is the most difficult skill for students to master. Students face difficulties in learning writing. They are not sure of how to arrange sentences into good paragraphs, how to develop their ideas, they have lack of vocabulary and tend to use only certain words they have known in writing. They also apply incorrect grammar in their writing. Teacher considers that teaching writing is a difficult task. This final project is about teaching writing recount text by using peer review technique to the eighth graders students of Junior High School 4 Batang in the academic year of 2014/2015. The aim of this study is to find out how peer review technique can be implemented to improve students’ skill in writing recount text. In order to achieve the objectives, an action research was designed and carried out in this study. The participants of this study were 38 students of class VIII D of SMP N 4 Batang in the academic year of 2014/2015. Questionnaire, observation sheet, and writing tests were used as the instruments for collecting data. The results of the study showed significant improvement of the students’ achievement in writing recount text. It is proven by the average results in every test; pre test (63.00), formative test (74.29), and post test (79.50). The students’ writing skill (organization, content, grammar, punctuation, and style and quality of expression) in each test improved, too. Moreover, the result of the observation sheet showed that peer review technique changed the students’ learning behavior being better than before. Their enthusiasm during the learning process increased in each cycle. The analysis result of questionnaire showed that peer review technique was useful to most of students to improve their learning interest in writing recount text. Their perception changed positively after having the treatment. It meant that the use of peer review technique could ease their problem in writing English especially recount text Based on the results of those research instruments, it can be concluded that using peer review technique as a learning technique gives the improvement to students’ skill in writing recount text.